Heparan sulphate inhibition of cell proliferation induced by TGFβ and PDGF - lan E. Silber; Jeanine M. Walenga; Jawed Fareed; Elizabeth J. Kovacs (Mediators of Inflammation)
The effect of glycosaminoglycans (GAGs) on the proliferation of smooth muscle cells (SMC) and fibroblasts was assessed by culturing cells with or without GAGs. Porcine heparan sulphate (HS) inhibited proliferation in a dose dependent manner. At 167 μg/ml of HS this reached 88% and 72% inhibition of SMC and fibroblast growth, respectively. Pig and beef mucosal heparins also blocked proliferation, but to a lesser extent. In contrast, beef lung heparin, chondroitin sulphate, and dermatan sulphate failed to block growth factor induced proliferation. Continuous presence of HS was not required, suggesting that the inhibitory effects resulted from a direct effect on the cell rather than an interaction of the GAG with growth factors. The mechanism by which GAGs inhibit proliferation will be addressed in future studies.